(untitled) (KULT_online, 2014)
In her book Anja Kangiesser focuses on anti-capitalist art-activist practices from the Berlin Dadaists to the recent actions revolving around issues of precarisation of life and labour, privatisation, migration, and commercialisation of higher education. Her focus is neither the specific aesthetics of such political actions, nor the political potential of their artistic approaches; rather she focuses on how such practices transverse traditionally firmly set categories of art and politics, performer and audience, activist and non-activist, in order to engage them in an active play with and against each other towards unforeseen political and artistic effects. And while the chosen theoretical framework for thinking the transversal between arts and politics remains entirely in place without being significantly rethought or reformulated, it is questionable how much her writing manages to entertain the stated tension of this transversal. Yet this ambiguity, as the author makes clear, might be constitutive for transversality itself.